Geographies of youth, mobile phones, and the urban hustle. - Amankwaa, Ebenezer Forkuo; Esson, James; Gough, Katherine V. (Geographical Journal, 2020)
Geographers have shown how mobile phones are transforming urban economies in Africa by altering the temporal and spatial nature of commercial transactions. Less well documented is how young people in Africa are using mobile phones to navigate the interplay between personal hopes, social expectations, and financial uncertainty associated with urban life. Drawing on qualitative data from youth in two Ghanaian cities, and insights from literature on youth geographies, hustling, and everyday urbanism, this paper explores how young people use mobile phones to conjure up and sustain social relations and income‐generating opportunities in urban settings. Three significant thematic findings emerge from our empirical data: the role of mobile phones in shaping young people's social status and responsibilities; the use of mobile phones as instruments for surveillance and relationships; and the use of mobile phone technologies as assets for realising income‐generating opportunities. Conceptually, our exploration of mobile phone usage furthers geographical scholarship by providing new insights on the multidimensional nature of constraints faced by youth and their strategies to overcome them. Furthermore, the incorporation of a comparative element within the study illustrates the need for a more spatially nuanced understanding of young people's uptake and use of mobile phone technologies.